The Effects of Radish (Raphanus sativus) Fruit Paste Substitution and Boiling Time on the Quality of Wet Noodles - Muhardina, Virna; Sari, Putri Meutia; Safiah, Safiah; Aprita, Ika Rezvani (Serambi Journal of Agricultural Technology, 2025)
The use of radish paste as a substitute for wet noodles has the potential to reduce dependence on imported wheat flour while increasing the nutritional content of the product. This study aims to examine the effect of radish paste substitution and boiling time on the quality of wet noodles, especially on water content, ash content, color, and texture. The method used was a Completely Randomized Design with two factors, i.e the concentration of radish pastes (15%, 20%, and 25%) and boiling time (2, 4, and 6 min). The results showed that water content and ash content were significantly influenced by both factors, although they did not significantly affect sensory evaluation. The highest water content was found in noodles with a substitution of 25% radish paste and a boiling time of 6 minutes, while the highest ash content occurred in the combination of 15% radish paste and a boiling time of 4 minutes. The hedonic test showed that the best color was obtained in the combination of 15% radish paste with a boiling time of 2 minutes, while the most preferred texture was in the treatment of 25% radish paste with a boiling time of 6 minutes. Thus, the use of radish paste as a substitute with the right boiling time setting can improve the quality of wet noodles optimally and be accepted by consumers